CMOS pixel sensors optimized for large ionizing dynamic. (1st September 2022) - Ren, W.; Baudot, J.; Federici, L.; Finck, C.; Hu-Guo, C.; Kachel, M.; Reidel, C.-A.; Schui, C.; Sefri, R.; Spiriti, E.; Weber, U.; Zhao, Y.
Abstract: Monolithic active pixel sensors (MAPS) are now well established as a technology for tracking charged particles, especially when low material budget is desirable. For such applications, sensors focus on spatial resolution and pixels with digital output or modest charge measurement ability are well suited. Within the European Union STRONG-2020 project, which focuses on experiments using hadrons, the TIIMM (Tracking and Ions Identifications with Minimal Material budget) joint research activity intends to expand granular MAPS capacity to energy-loss (Δ E ) measurement for ion species identification. The TIIMM prototypes are developed in the Tower Jazz 180 nm CMOS image sensor (CIS) process. The Time-Over-Threshold (ToT) method is applied to the sensor for the energy-loss measurement. The main design details and the preliminary test results from laboratory measurements of the initial TIIMM prototype are presented in this work.